Shot on location eaudiobook Key west series, book 9. - Shames, Laurence (Key West, 2015)
Take three speedboats, a disgruntled ghostwriter, and a hit TV show starring a gorgeous but impossible diva and created by a driven genius who may be losing his marbles. Add a fearless and gleefully profane stuntwoman, an ancient Mafioso with a chihuahua, and a revenge-crazed blonde in gladiator sandals. Stir in a thug with a heart of gold and an inveterate slacker who yearns for glory. Whisk a loopy but tender romance into the mix, turn the whole crew loose in the liberating and seductive sunshine of the Florida Keys-and what do you have? SHOT ON LOCATION, the new and long-awaited Key West novel by Laurence Shames. Hilarious and suspenseful, wisecracking and wise, this is the most intoxicating story yet from the author of such cult classics as FLORIDA STRAITS and SUNBURN. Longtime Shames fans will rejoice at his return to the fictional turf of Key West and the reappearance of some of his most beloved characters. And new readers will find themselves in for a hell of a ride as Hollywood glitz meets Florida funky.